Health locus of control is associated with medication adherence among outpatients with type 2 diabetes mellitus in Jakarta, Indonesia - Dita Ayu Setiya Wati; Wilda Fauzia (Malahayati International Journal of Nursing and Health Science, 2026)
Background: The increasing number of patients with type 2 diabetes each year indicates that early and sustained diabetes management is essential, particularly adherence to antidiabetic medication. Medication adherence in patients can be influenced by various factors, one of which is health locus of control. Purpose: To determine the relationship between health locus of control and medication adherence among outpatients with type 2 diabetes mellitus. Method: A cross-sectional design was applied. Participants were recruited through purposive sampling, yielding a total of 103 respondents. Data were collected using structured questionnaires and analyzed with descriptive statistics and Spearman’s rho correlation test. Results: Analysis revealed a significant correlation between health locus of control dimensions and medication adherence. The chance health locus of control dimension demonstrated the strongest association, with a moderate correlation coefficient (r = 0.453, p = 0.001). Internal health locus of control showed a weaker correlation (r = 0.296, p = 0.004), while the powerful others dimension also exhibited a weak correlation (r = 0.296, p = 0.002). Conclusion: Among the three dimensions, chance health locus of control showed the largest observed correlation with medication adherence, showing a moderate correlation with medication adherence. These findings suggest that interventions should prioritize enhancing patients’ awareness of controllable health factors to strengthen adherence to antidiabetic therapy.